DESIGNING A WEB-BASED COMPANY PROFILE AS A MARKETING FACILITY AT PT KLS - Bajsair, Faik; Baisyir, Fauzi; Hardiansyah, Novi (Universitas Trilogi, 2025)
The increasing need for an effective digital presence has driven the optimization of the Company profile site at PT. KLS. This study aims to analyze and improve the usability of the website using the Research Flow method in the marketing and promotion process. The research began with a comprehensive needs analysis, followed by prototype testing, and concluded with implementation and evaluation. A user survey was conducted involving 100 respondents to assess navigation ease, design appeal, and information clarity. The results show that 82% of users find this website more effective than previous marketing methods, with a usability score of 4.3 out of 5. The main improvements include optimized responsiveness and better content organization. This study contributes to the development of a structured website design methodology that enhances user engagement and business credibility